1997
DOI: 10.2466/pr0.1997.81.3.781
|View full text |Cite
|
Sign up to set email alerts
|

Locus of Control of Smokers, Nonsmokers, and Nonpractising Smokers

Abstract: In this survey, score analyses of 123 male and female respondents, ages 21 to 33 years, yielded no significant differences between either sex and smokers versus nonsmokers on Rotter's locus of control scale. Of particular interest was that nonpracticing smokers (quitters) scored more internal than either smokers or nonsmokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Indeed, whereas cross-sectional research has found internal locus of control to be greater among ex-smokers than current smokers and individuals who have never smoked (Molloy et al, 1997), prospective research has not found internal locus of control to be a predictor of smoking cessation (Matheny & Weatherman, 1998). It is conceivable that the sense of achievement an individual experiences given her or his success at quitting smoking reinforces her or his sense of control, or omnipotence.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, whereas cross-sectional research has found internal locus of control to be greater among ex-smokers than current smokers and individuals who have never smoked (Molloy et al, 1997), prospective research has not found internal locus of control to be a predictor of smoking cessation (Matheny & Weatherman, 1998). It is conceivable that the sense of achievement an individual experiences given her or his success at quitting smoking reinforces her or his sense of control, or omnipotence.…”
Section: Discussionmentioning
confidence: 99%
“…Each item scored from 1 (strongly disagree) to 6 (strongly agree) for the externally worded items and reverse scored for the internally worded items [28]. Those who have confidence that whatever happens to them is substantially within their domain of influence are said to have a predominantly internal locus of control, while those who believe that they are influenced by external forces are considered to have an external locus of control [29]. The Arabic version of the HLC was constructed and validated by Badr and Moody [6].…”
Section: Methodsmentioning
confidence: 99%
“…These studies identified that greater cigarette use and greater addiction to nicotine are related to stronger beliefs about external loci of control. While a more recent small study challenged this phenomenon regarding elevated levels of external locus of control among smokers compared to nonsmokers, others have argued that this solitary small study was too underpowered to sufficiently test for [13].…”
Section: Smoking and External Locus Of Controlmentioning
confidence: 99%